Caracterización de pozos petroleros aprovechables para la producción de energía geotérmica (2021)
In order to understand what are the most important properties for producing geothermal energy from an oil well, this document presents the generalities related to geothermal energy, from its main characteristics, to its classification and applications, both direct use of heat, as well as electricity generation, one of the most striking applications of this unconventional energy source. In addition, the technologies used to generate electrical energy from the geothermal resource are described. Some unconventional technologies are also presented, such as the use of oil wells for geothermal energy production in order to reduce costs and risks associated with the exploratory phase of a geothermal project, as well as the economic and environmental advantages that an oil project would gain from producing geothermal energy.